The effects of vortex shedding on the aerodynamic performance of airfoils - Sikien, Esther Rami; Abdullah, Aslam; Zulkafli, Mohd Fadhli; Rahim, Mohammad Zulafif (Asian Research Publishing Network (ARPN), 2018)
This is a comparative study involving various National Advisory Committee for Aeronautics (NACA) airfoils NACA 0012, NACA 0024, NACA 4412 and NACA 4424. The numerical simulation involves the air flow passing these models at high Reynolds number and various angles of attack. The study focuses mainly on the aerodynamic performance as represented by lift and drag coefficients. The Computational Fluid Dynamics simulation has been carried out in order to understand the phenomena of vortex shedding. The aim is to investigate the effects of vortex shedding on the aerodynamic performance of airfoils which has still been widely discussed over the years. The methodology has been validated; by using Spalart-Allmaras, K-epsilon and inviscid models, the first with the turbulence intensity and backflow of 0.10% contributed to relatively accurate result. The outcome reveals that there are few aspects that need to be considered in order to control or delay vortex shedding phenomena such as thickness-to-chord ratio, airfoil types, Reynolds number and whether or not it involves transient flow.